The effect of furnace steel slag powder on the performance of cementitious mortar at ambient temperature and after exposure to elevated temperatures. (October 2021) - Jihad Miah, Md; Kawsar Ali, Md.; Lo Monte, Francesco; Chandra Paul, Suvash; John Babafemi, Adewumi; Šavija, Branko
Abstract: Induction furnace steel slag is a secondary product obtained when molten steel is separated from the impurities in the steel-producing furnaces. Though numerous studies have been published on the mechanical strength of concrete/mortar made with steel slag as fine aggregate, relatively few studies focus on the shrinkage, durability (i.e., porosity, water absorption, and resistance to chloride penetration) at ambient temperature, and especially the mechanical and durability performances after exposure to elevated temperatures. Within this context, the present study investigates mechanical strength, shrinkage, and durability of mortar made with different contents of steel slag powder (SSP) at two different water-to-cement (w/c) ratios before and after exposure to elevated temperatures (120, 250, 400 and 600 °C). Mortars made with SSP showed significantly higher mechanical strength and better durability than mortar made with 100% natural sand (control mortar). Compressive, tensile, and flexural strength increased by 45%, 72% and 56%, respectively, when SSP entirely replaced natural sand. Porosity, water absorption, and chloride penetration decreased by 42%, 61% and 52%, respectively, for 100% SSP mortar. Furthermore, the shrinkage of the mortar decreased with increasing percentages of SSP. Conversely, residual compressive strength after heat exposure was lower for 100% SSP mortar than for the control mortar. Therefore, this study presents a first step towards the successful utilization of SSP in cementitious mortar.